CKD Patients’ Emotional Well-Being: An Examination of Their Psychological Stressors and Support Factors - Jairo N. Fuertes; Olivia B. Friedman; Michael T. Moore; Sofia Rubinstein (Kidney and Dialysis, 2025)
This study examined 112 CKD patients’ adherence to and satisfaction with treatment, and their quality of life, as mediated by the level of psychological stress experienced as well as their working alliance, resilience, and social support. The patients were receiving care at a public teaching hospital in the northeast region of the U.S. The results indicated a significant moderate negative correlation between psychological distress and quality of life (r = −0.34, p < 0.01). The results also indicated significant positive moderate to strong correlations between the physician–patient working alliance and adherence (r = 0.42, p < 0.001), satisfaction (r = 0.55, p < 0.001), and quality of life (r = 0.51, p < 0.001), between social support and quality of life (r = 0.39, p < 0.001), and significant moderate positive correlations between resilience and adherence (r = 0.35, p < 0.001) and satisfaction (r = 0.26, p < 0.01). Regression analyses indicated that the following predictors were significant: patient adherence was positively predicted by the working alliance (β = 0.42, p < 0.001); patient satisfaction was positively predicted by the working alliance (β = 0.51, p < 0.001) and negatively predicted by psychological distress (β = −18, p < 0.048); and quality of life was positively predicted by the working alliance (β = 0.38, p < 0.001) and social support (β = 0.28, p < 0.016) and negatively predicted by psychological distress (β = −0.34, p < 0.002). Moderation analyses indicated that the working alliance moderated the relationship between COVID impact and adherence (R2 = 0.27, F(df1, df2) = 8.36, p < 0.001, 95% CI = 0.29–2.74), social support moderated the relationship between COVID impact and adherence (R2 = 0.19, F(df1, df2) = 5.77, p < 0.001, 95% CI = 0.47–2.77), and resilient coping moderated the relationship between COVID impact and satisfaction (R2 = 0.20, F(df1, df2) = 7.89, p < 0.001, 95% CI = 0.94–2.81). The present study provides evidence of the significant role of psychological stressors and social support in influencing CKD patients’ adherence to and satisfaction with treatment, as well as their quality of life.